Electromagnetically Navigated Tube Placement Device for Bedside Placement of Small Bowel Feeding Tube on Patients with Acute Severe Pancreatitis: Comparative Study - Tan, Guoliang; Chen, Yongming; Lin, Yanping (Current Medical Imaging, 2024)
BackgroundA developing approach for the bedside installation of feeding tubes is the Electromagnetic Navigation-assisted Tube Placement Device (ENTPD). The ENTPD monitors the tip position of feeding tubes when they are inserted into the digestive tract. It aids in the avoidance of airway misalignment and allows placing into the small bowel. Several recent exploratory studies have shown that ENTPD for nasojejunal feeding tube installation can improve success rates, lower costs, and allow for a more rapid beginning of enteral nutrition.ObjectivesThe aim of this study was to compare the effect of using an ENTPD for bedside placement of small bowel feeding tubes with blind placement on patients with acute severe pancreatitis and to see how well the electromagnetic navigation trajectory image (ENTI) and X-ray agreed on the location of the tube tip after placement.MethodsThe study was done prospectively using randomized and single-blind methods. The 65 cases used electromagnetic navigation-assisted placement, and 58 cases were blind placement. For judging the tube tip location, we compared the success rate, median time, number of repeat placements, complications, and agreement of ENTI vs. X-ray.ResultsThe blind placement group's success rate was 86.21% compared to the ENTPD's 95.38%, P = 0.075. The median time was significantly longer in the blind placement group (116.55 ± 68.62 min vs. 25.37 ±12.63 min, P=0.000); the average number of repeating placements was 3.02 ± 1.21 vs. 1.16 ± 0.31 (Blind placement vs. ENTPD, P = 0.002). It provided a high degree of agreement between ENTI and X-ray after contrast, κ=0.752 [95% confidence interval, 0.67-0.84]. No complications occurred in the two groups.ConclusionENTPD was used safely and effectively at the bedside to help patients with acute severe pancreatitis get feeding tubes. It not only improved the high successful rate of placement, decreased the time and reduced the exposure to X-ray, but it was also very convenient for bedside placement because of the portable equipment.
Keywords: Acute pancreatitis